The Paraventricular Thalamus as a Critical Node of Motivated Behavior via the Hypothalamic-Thalamic-Striatal Circuit - Iglesias, Amanda G.; Flagel, Shelly B. (Frontiers in Integrative Neuroscience, 2021)
In this review, we highlight evidence that supports a role for the paraventricular nucleus of the thalamus (PVT) in motivated behavior. We include a neuroanatomical and neurochemical overview, outlining what is known of the cellular makeup of the region and its most prominent afferent and efferent connections. We discuss how these connections and distinctions across the anterior-posterior axis correspond to the perceived function of the PVT. We then focus on the hypothalamic-thalamic-striatal circuit and the neuroanatomical and functional placement of the PVT within this circuit. In this regard, the PVT is ideally positioned to integrate information regarding internal states and the external environment and translate it into motivated actions. Based on data that has emerged in recent years, including that from our laboratory, we posit that orexinergic innervation from the lateral hypothalamus (LH) to the PVT encodes the incentive motivational value of reward cues and thereby alters signaling of the glutamatergic neurons projecting from the PVT to the shell of the nucleus accumbens (NAcSh). The PVT-NacSh pathway then modulates dopamine activity and resultant cue-motivated behaviors. As we and others apply novel tools and approaches to studying the PVT we will continue to refine the anatomical, cellular and functional definitions currently ascribed to this nucleus and further elucidate its role in motivated behaviors.